2002
DOI: 10.1124/dmd.30.8.931
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residues Affecting the Activities of Human Cytochrome P450 2C9 and 2C19

Abstract: ABSTRACT:The amino acid residues affecting the substrate specificity of human cytochrome P450 CYP2C9 and CYP2C19 for their metabolic activities were investigated using chimeras and mutant enzymes, which were constructed by replacing the corresponding residues. Although CYP2C19 showed nearly the same tolbutamide hydroxylase activity as CYP2C9, the activities for the CYP2C19(H99I) mutant and the chimeras that replaced residues 1-212 were much lower than those for CYP2C19. The activities of the CYP2C19(H99I) muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…Interestingly, CYP2C19 and CYP2C9 have very distinctive substrate specificities, although they are the most highly conserved (91% amino acid sequence identity) among human CYP2C enzymes (Romkes et al 1991;Goldstein and de Morais 1994;Miners et al 2000;Tsao et al 2001). For example, His99 of CYP2C19 and Ile99 of CYP2C9 in SRS-1 have been speculated to be important residues for substrate binding (Ibeanu et al 1996;Niwa et al 2002). The amino acids of interest in this study, Arg329 and Ser51, are located in the J and A helices, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, CYP2C19 and CYP2C9 have very distinctive substrate specificities, although they are the most highly conserved (91% amino acid sequence identity) among human CYP2C enzymes (Romkes et al 1991;Goldstein and de Morais 1994;Miners et al 2000;Tsao et al 2001). For example, His99 of CYP2C19 and Ile99 of CYP2C9 in SRS-1 have been speculated to be important residues for substrate binding (Ibeanu et al 1996;Niwa et al 2002). The amino acids of interest in this study, Arg329 and Ser51, are located in the J and A helices, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…11) Further, residues 237 and 286 were suggested to play important roles in (S)-mephenytoin 4′-hydroxylation, 12,14) and replacement of asparagine 286 with serine (N286S) enhanced tolbutamide p-methyl hydroxylase, diclofenac 4′-hydroxylase, and ibuprofen hydroxylase activities. 16) Moreover, the CYP2C19 KSN triple mutant (E241K/N286S/I289N) was reported to metabolize both (R)-and (S)-warfarin with a broadened regioselectivity.…”
Section: Discussionmentioning
confidence: 99%
“…# These authors contributed equally to this work. residues as key determinants for omeprazole 5-hydroxylase activity, 11,12) (S)-mephenytoin 4′-hydroxylation, 13,14) and binding and metabolism of warfarin, 15) diclofenac, and ibuprofen. 16,17) It is noteworthy that the role of CYP2C19 residues glutamic acid 72 (Glu72) and glutamic acid 241 (Glu241), and CYP2C9 residues lysine 72 (Lys72) and lysine 241 (Lys241) in metabolic activity and binding affinity for TCA drugs, as well as basic drugs, has not been investigated.…”
mentioning
confidence: 99%
“…We previously demonstrated that several human hepatic P450s, including CYP2C8, CYP2C9, and CYP2C19, exhibit aminopyrine Ndemethylation activity (16). Tolbutamide is a typical substrate of CYP2C9 in vitro and a probe drug used for in vivo drug interaction studies as recommended in the guidance by EMA (19) and by FDA (20); however, tolbutamide methylhydroxylation was catalyzed by not only CYP2C9 but also CYP2C19 (8). In the present study, CYP2C19 showed a higher Km and Vmax than that shown by CYP2C9 and the Vmax/Km value for CYP2C19 was twice that of CYP2C9, whereas methylhydroxylated tolbutamide catalyzed by CYP2C8 was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP2C subfamily in human liver comprises three members: CYP2C8, CYP2C9, and CYP2C19. Although the three CYP2C enzymes share more than 82% amino acid sequence identity, they have rather distinct substrate specificities (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%